Tingkat Efektivitas Penggunaan Video Pembelajaran Terhadap Hasil Belajar Siswa Kelas VII Tentang Bentuk Muka Bumi dan Aktifitas Penduduk Indonesia Di Smp Negeri 3 Teras Boyolali - EDI WIBOWO, EKO (2016)
The study was conducted in SMP Negeri 3 Teras Boyolali Tawangsari Village, Boyolali District of Boyolali. Each of the learning process must pay attention to the media which shall be used for learning to walk with an active and effective. The purpose of this study was to determine the effectiveness of instructional video media in the form of earth material and activities of the Indonesian population class VII SMP Negeri 3 Teras Boyolali Year 2014/2015. This research method is experimental class VII SMP Negeri 3 Terrace Boyolalidengan number as many as 180 students. Sixth grade classes are divided into experimental and control classes. Experimental class as much as 1 class in the learning process using instructional video media. While the control class as well as first class in the learning process using conventional strategies such as lectures. The results of this study concluded that (1) The use of instructional video media can be used to improve student learning outcomes in social studies bentukmukabuumi danaktivitaspenduduk Indonesia due to improved learning outcomes experimental class is higher than the control class. In the post-test and pre-test experimental class increased by 10.82%, whereas in the control group increased by 8.4%. (2) The results of studying the experimental class control class shows their difference. The average value of classroom experiments using video media pembelajaranmemiliki value post test80,62% while the control class average value of post test of 58.33%, thus Ho is rejected and Ha accepted. The difference of the class indicates that the use of video media pembelajaranlebih effective compared to conventional models